CHARACTERISTICS OF PATIENTS WITH TYPE 2 DIABETES MELLITUS AT SURABAYA HAJI GENERAL HOSPITAL - Ismianti Lifia Bestari (The Indonesian Journal of Public Health, 2020)
Diabetes mellitus is a chronic disease due to impaired blood glucose levels. Type 2 diabetes mellitus dominantly causes most deaths in the world. The number of patients with type 2 diabetes mellitus (DM) was ranked the second highest at the Surabaya Haji General Hospital. Purpose: This study described characteristics of patients with type 2 DM at  the Surabaya Haji General Hospital. Methods: This study was descriptive and used a cross-sectional research design. This study’s population were patients with type 2 DM who visited Diabetes Unit at Surabaya Haji General Hospital. This study was conducted in the Diabetes Unit at the Surabaya Haji General Hospital by involving 114 respondents as the samples. These respondents were interviewed using questionnaires from 11 March to 11 April 2019. The study’s variables were patients’ characteristics including age, gender, family history, and disease duration. Data were analyzed using a univariate analysis with a frequency table. Results: Almost all of patients with type 2 DM at  Surabaya Haji General Hospital were aged ≥40 years (94.7%) and female (71.9%). The majority of patients had a family medical history of type 2 diabetes mellitus disease (60.5%) and long disease duration of >5 years (5.,4%). Conclusion: Almost patients with type 2 DM in  Surabaya Haji General Hospital were elderly who had a family medical history of diabetes mellitus and had suffered from type 2 diabetes mellitus for >5 years.Keywords: diabetes mellitus, characteristics, hospital, descriptions.